Peningkatan Hasil Belajar IPA Materi Energi dan Perubahannya dengan Menggunakan Metode PAIKEM pada Siswa Sekolah Dasar - Habibah Siregar; Masrul Masrul; Musnar Indra Daulay (Journal on Education, 2022)
This research originates from the fact that many students in grade II SD are still not focused on participating in learning, especially in class II A SD Negeri 007 Tambusai. The results of learning science in class II A are very low, this is because students often do not understand what the teacher conveys, because the teacher also lectures more, and many students are still passive. So that the teaching and learning process does not go well, where students are bored because the learning conditions are not pleasant. One solution to overcome this problem is to use the PAIKEM method. The PAIKEM method is one of the learning methods that can improve science learning outcomes, and thus the purpose of this study was to describe the increase in science learning outcomes for class II A students at SD Negeri 007 Tambusai on energy and its changes. This study uses a qualitative and quantitative approach to the form of research, namely Classroom Action Research (CAR). This research was carried out in two cycles and each cycle was held in two meetings. This research was conducted at SD Negeri 007 Tambusai, with research subjects being class II A SD. Collecting data in this study using observation techniques, tests, documentation, and field notes. Data were analyzed using qualitative data analysis proposed by Arikunto which consisted of data induction, data description, and conclusions. The increase in Science Learning Outcomes in energy material and its changes using the PAIKEM method in each cycle can be seen from the average score of 74.61 with a learning completeness percentage of 53.84 in cycle I and an average score of 81.92 with a learning completeness percentage of 88.46 in cycle II. So, the PAIKEM method can improve science learning outcomes in energy material and its changes in class II A SD Negeri 007 Tambusai.